Cardiovascular Health in Professional Rugby Union Athletes - Mchugh, Cliodhna Mary (Trinity College Dublin. School of Medicine. Discipline of Physiotherapy, 2021)
Cardiovascular disease (CVD) defines a class of diseases relating to the heart and blood vessels, including coronary heart disease, coronary artery disease and hypertension. CVD risk and outcomes can be managed through modifiable risk factors, including healthy diet, physical activity, not smoking, normal body weight, and normal levels of total cholesterol, blood pressure and fasting blood glucose. Athletes are often regarded as a model of health, through the lifestyle behaviours associated with elite athleticism. There has been a growing interest in the benefits and risks associated with high volumes of exercise, with a focus on the relationship between exercise and cardiovascular health, particularly in sports where increased body size is common. Rugby athletes often engage in intentional and prolonged maintenance of elevated body mass, attributable to variances in lean mass and adipose tissue. The demands required to be successful in rugby lead to adaptations to cardiovascular physiology, which may expose these athletes to CVD risk. Therefore, the primary aim of this PhD thesis was to investigate the cardiovascular health of professional rugby athletes by investigating the prevalence of CVD risk factors and the implications associated with rugby participation on long-term cardiovascular health. This thesis commenced with a systematic review of the cardiovascular health of retired field-based athletes. Retired athletes with elevated playing time body mass had an increased prevalence and severity of CVD risk factors, including increased systolic blood pressure, low-density lipoprotein, cardiometabolic syndrome and carotid artery calcium. Findings suggested that prior engagement in field-basedsports does not provide long-term protection from CVD. Following this was a second systematic review of the cardiovascular health of current field-based athletes. Elevated levels of CVD risk in some athletes, primarily American football athletes was identified. Lifestyle behaviours associated with elite athleticism, particularly in athletes with increased body mass, expose athletes to greater metabolic and CVD risk, which is not completely offset by sport participation. Findings suggest that athletes who engage in deliberate body mass gain for performance benefits may be exposed to increased CVD risk. Study I aimed to assess longitudinal body composition changes in rugby athletes and to determine if supersizing of athletes was present over a 7- year period. Although no significant body composition trends were apparent, findings revealed a modest increase in lean mass and a modest reduction in body fat percentage. While mass is an integral component to performance in rugby, athletes with increased mass were found to have a greater propensity to have body fat percentage above desired healthy ranges. Study II was designed to investigate visceral fat and changes to visceral fat in relation to other indices of body composition. No association was identified between body fat percentage or visceral fat and BMI, rejecting our hypothesis that visceral fat would display concomitant changes with body fat percentage. Decreases in body fat percentage did not necessarily reflect changes to visceral fat and reduction may be caused by subcutaneous fat loss. Moreover, a total mass threshold (116.04 kg) was identified beyond which lean mass accumulation decreased and body fat percentage and visceral fat increased.Athlete electrocardiogram (ECG) interpretation is nuanced and normative values have not been previously established for rugby athletes. Current preparticipation guidelines from World Rugby endorse but do not mandate the inclusion of an ECG. Therefore, Study III was designed to examine sport-specific normative ECG values and evaluate positivity rates using the 2018 international recommendations for ECG interpretation in athletes. Training-related ECG features were common in rugby athletes, including incomplete right bundle branch block, sinus bradycardia, sinus arrhythmia, early repolarisation, increased QRS voltage and first-degree atrioventricular block. The low positivity rate identified (2.4%) highlights the importance of clinically effective interpretation of athletes ECGs; understanding that chronic exposure to high intensity exercise results in several cardiac adaptations that are reflected on an ECG. Therefore, the prevalence and nature of training-related features identified in this cohort is similar to normative findings reported in athletes from other sporting disciplines. Study IV assesed the prevalence of CVD risk factors in professional rugby athletes. One fifth of athletes were found to have no cardiovascular risk factors. 74% of athletes had at least one risk factor: 50% with one- to -two risk factors and 24% with three- to -four risk factors. The most prevalent risk factors, included elevated Creactive protein, hypertension and dyslipidemia categorised by low high-density lipoprotein. An increase in body fat percentage and forward position were associated with a 2.7 and 1.8 increased odds ratio of having a higher number of risk factors, respectively. Rugby forwards who engage in predominately isometric activity, demonstrated a level of CVD risk that is comparable to linemen in American football. Findings indicate that professional rugby athletes are not insusceptible toCVD risk factors, most notably, hypertension, dyslipidemia and elevated C-reactive protein. Collectively, the studies in this thesis investigated the overall cardiovascular health profile of professional rugby athletes by exploring the prevalence of CVD risk factors and the implications associated with rugby participation on long-term cardiovascular health. Findings from Study I and Study II may be used to understand the role of body composition indicies and increasing body mass of rugby athletes. It is hoped that findings from Study III will be used for the development of normative values and inform the potential benefits of ECG inclusive screening in rugby athletes. Study IV findings detail an underestimated and unexpected level of CVD risk in professional rugby athletes. Further research is required to evaluate the prognostic impact on cardiovascular health, particular those of larger size.
APPROVED
Keywords: Cardiovascular Health; CVD Risk Factors; Cardiometabolic Disease; Electrocardiograms; Athletes; Rugby